KARAKTERISTIK KOMPOSISI ASAM LEMAK PADA BIJI KAKAO DARI 12 DAERAH DI SULAWESI SELATAN - Ristanti, Eky Yenita; Suprapti, Suprapti; Anggraeni, Dhenok (Balai Besar Industri Hasil Perkebunan, 2016)
Fatty acids are among the important characteristics of cocoa in the industry. The compositionof fatty acids in cocoa butter contributes to the hardness of cocoa butter. This research aims to know thecharacteristics of cocoa bean obtained from 12 regions in South Sulawesi. Fatty acids were analyzedusingg as chromatography. The results showed that the dominant fatty acids in cocoa bean were stearicacid, oleic acid, and palmitic acid, whereas highest fatty acids contents were found in cocoa beans fromSinjai Region and the lowest one were found in cocoa beans from Soppeng Region.Keywords: Fatty acids, Cocoa Beans, Composition, Gas Chromatography, SouthSulawesi